Crystal Structure of Elongator Subcomplex Elp4–6 - Lin, Zhijie (American Society for Biochemistry and Molecular Biology, 2012)
Elongator is a multiprotein complex composed of two subcomplexes, Elp1–3 and Elp4–6. Elongator is highly conserved between yeast and humans and plays an important role in RNA polymerase II-mediated transcriptional elongation and many other processes, including cytoskeleton organization, exocytosis, and tRNA modification. Here, we determined the crystal structure of the Elp4–6 subcomplex of yeast. The overall structure of Elp4–6 revealed that Elp6 acts as a bridge to assemble Elp4 and Elp5. Detailed structural and sequence analyses revealed that each subunit in the Elp4–6 subcomplex forms a RecA-ATPase-like fold, although it lacks the key sequence signature of ATPases. Site-directed mutagenesis and biochemical analyses indicated that the Elp4–6 subcomplex can assemble into a hexameric ring-shaped structure in vitro and in vivo. Furthermore, GST pulldown assays showed that the ring-shaped assembly of the Elp4–6 subcomplex is important for its specific histone H3 binding. Our results may shed light on the substrate recognition and assembly of the holo-Elongator complex.